Securely verifiable outsourcing schemes of matrix calculation. (2015) - Xiang, Can; Tang, Chunming
Matrix calculation, which has been considered as one of the most expensive operations, plays an important role in most current cryptosystems. In this paper, we propose three new and secure outsourcing schemes of matrix calculation by using one untrusted cloud server. The first one is for matrix multiplication, the second is for the inverse of a matrix, and the third is for the determinant of a matrix. Compared with other proposed schemes, our schemes are superior in efficiency owing to the reduction of user cost. In particular, the user's computation cost in our schemes is at most 1/4, 1/4, 7/16 of the corresponding schemes in the state-of-the-art algorithms, respectively. In addition, the efficiency and security of our schemes are analysed and proved.